Mortality and exacerbation risk according to GOLD and STAR severity stages of COPD: a 5-year multicenter prospective cohort study - Hiroaki Ogata; Kazuya Tsubouchi; Tomotsugu Takano; Katsuyuki Ichiki; Ryo Torii; Shohei Takata; Noriaki Nakagaki; Makoto Yoshida; Yasuhiko Kitasato; Kazunori Tobino; Eiji Harada; Hiroshi Wataya; et al. (Scientific Reports)
Abstract The Global Initiative for Chronic Obstructive Lung Disease (GOLD) classification, based on percent predicted forced expiratory volume in 1 s (ppFEV1), has been widely adopted for assessment of chronic obstructive pulmonary disease (COPD) severity. However, the STaging of Airflow obstruction by Ratio (STAR) system, based on the ratio of FEV1 to forced vital capacity, was recently proposed as an alternative classification. This study aimed to compare the prognostic performance of the GOLD and STAR classifications for prediction of mortality and exacerbation risk in individuals with COPD. This 5-year prospective, multicenter cohort study enrolled 370 individuals with COPD at 29 medical centers. All-cause mortality risk across GOLD and STAR stages was evaluated with Kaplan-Meier curves and Cox proportional hazards models. The risk of moderate to severe COPD exacerbations across GOLD and STAR stages was examined with cumulative incidence function (CIF) curves and Fine and Gray models. Both classification systems showed a significant association with mortality and exacerbation risk (P < 0.01 for trend). The GOLD classification provided a better separation of Kaplan-Meier and CIF curves for advanced stages, whereas the STAR classification showed a clearer distinction between stages I and II. These associations remained consistent after multivariable adjustments. The GOLD classification was superior for prediction of prognosis in advanced COPD, whereas the STAR classification provided better differentiation in early-stage disease. These findings highlight the complementary roles of the GOLD and STAR classifications in assessment of COPD severity.